Repetitive control of functional electrical stimulation for induced tremor suppression. (December 2015) - Freeman, C.T.; Sampson, P.; Burridge, J.H.; Hughes, A.-M.
Abstract: Tremor is an involuntary, oscillating, debilitating movement which affects over 50% of people with Multiple Sclerosis. In this paper an advanced paradigm, combining linearising action and repetitive control (RC), is developed to suppress tremor using functional electrical stimulation (FES) applied to wrist extensors/flexors. This innovative biomechanical approach to tremor suppression embeds learning from experience, and its effectiveness is confirmed in tests performed with nine healthy adults who attended a single one-hour session. Using FES, pathological wrist tremors (2.5, 3 or 4 Hz) were induced via extensor digitorum and a validated mechanical wrist-rig was used to collect data. Results confirmed statistically significant reduction in pathological movement, measured by path-length wrist movement and single peak amplitude of tremor.